Low-cost solar tracking with LDR-based sensing: optimizing energy harvest for domestic applications - Hasni, Nur Syamilaini Binti Mohd; Rahman, Zubaidah Binti Abdul; Ibrahim, Mohd Hafizuddin Bin (Indonesian Institute for Counseling, Education, and Therapy (IICET), 2024)
Solar panels have been widely used in recent years in converting solar energy to electrical energy. To maximize the conversion of solar energy to electrical energy, the solar panel should always be in a position perpendicular to the sun. The main goal of this project is to design a solar tracking system that can detect the position of the sun in turn converting and storing solar energy to electrical energy to the maximum. In this project, the solar tracker moves 60 degrees from east to west and vice versa. The project involves the development of hardware and software for simulation testing. The system consists of Arduino Uno, servo motor, Light Dependent Resistor (LDR) as sensor and solar panel. Ihe impact of this project can reduce operating costs for the production of electricity using fuel.